Using ancillary ligands to tune the DNA binding properties of self-assembled luminescent metallomacrocycles - Ahmad, Haslina; Ghosh, Dipesh; Thomas, Jim A. (Royal Society of Chemistry, 2014)
The optical response, binding parameters, and duplex DNA binding mode of water-soluble kinetically inert tetranuclear metallomacrocycles can all be controlled by judicious selection of ancillary ligands.